Genetic parameter estimates for birth and weaning weights, pre-weaning daily weight gain and tree type traits for Charolais beef cattle in Spain - El-Saied, U.M.=700 1 De la Fuente, L.F.; Rodriguez, R.; San Primitivo, F.
(Es, En)
ilus., 30 ref.
Keywords: PARAMETROS GENETICOS; CORRELACION GENETICA; ANATOMIA ANIMAL; HEREDABILIDAD; GANADO BOVINO; ESPAÑA